2003
DOI: 10.1007/s00535-002-1090-7
|View full text |Cite
|
Sign up to set email alerts
|

Type C-chronic hepatitis patients who had autoimmune phenomenon and developed jaundice during interferon therapy

Abstract: Of a total of 2342 patients with type-C chronic hepatitis treated with interferon (IFN) at this hospital, 3 patients developed jaundice during the course of IFN therapy, but all 3 of them exhibited negative conversion of hepatitis C virus (HCV)-RNA following readministration of IFN. All 3 patients were assessed as having "probable autoimmune hepatitis (AIH)" in accordance with the AIH scoring system, indicating association with an "autoimmune phenomenon". Readministration of IFN at a low-dose induced activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…In the present study, serum ALT and AST level were significant elevated in ANA positive group than ANA negative group (pvalue > 0.0001).This results come in accordance with Sezaki et al who reported that ALT level is higher in patients with autoimmune diseases (Sezaki et al, 2003).…”
Section: P=0009supporting
confidence: 91%
“…In the present study, serum ALT and AST level were significant elevated in ANA positive group than ANA negative group (pvalue > 0.0001).This results come in accordance with Sezaki et al who reported that ALT level is higher in patients with autoimmune diseases (Sezaki et al, 2003).…”
Section: P=0009supporting
confidence: 91%
“…With regard to the treatment of autoimmune hepatitis induced by IFN, corticosteroid is reported to be effective [5,6,15]. In our patient, her ALT level began to decrease immediately after the administration of 500 mg of methylprednisolone, and her total bilirubin level also gradually decreased after the beginning of the therapy.…”
Section: Discussionmentioning
confidence: 71%
“…Of a total of 2,342 chronic hepatitis C patients treated with IFN in their institute, only 3 patients (0.1%) developed jaundice during or after IFN treatment, and they concluded that jaundice rarely develops in patients with hepatitis C during or after IFN therapy [6]. They also reported that the 3 patients had an autoimmune score of "probable AIH" prior to the initiation of IFN therapy and therefore that autoimmune scoring before IFN therapy would be a useful tool for predicting the development of autoimmune hepatitis [6]. However, in daily practice, it is not practical to investigate HLA haplotype and liver histology in all patients who undergo IFN therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both total protein and albumin were normal (6.4 and 4.0 g/dL, respectively). However, the TSH was very low, at 0.03 µIU/L (normal, 0.5-5.5 µIU/L); total T3 was mildly elevated, at 179.12 ng/dL (normal, 87-178 ng/dL); T4 was 8.9 µg/dL (normal, 6.09-12.23 µg/dL); and free T4 was [9][10][11][12][13][14] Multiple + (80%) + (72%) Minocycline [15][16][17][18][19][20][21] Multiple [24][25][26][27] Multiple [41][42][43][44] IR + + Atorvastatin [45,46] IR + + Germander [47,48] IR + + Propylthiouracil [49][50][51][52] IR + + Diclofenac [53,54] IR + − Pemoline [55] IR + − Antimicrosomal Doxycycline [56] IR + − Benzarone [57] IR − + Fenofibrate [58] − − Dai-saiko-to (herb) [59] IR + +…”
mentioning
confidence: 99%